Volume 9: 23rd International Conference on Design Theory and Methodology; 16th Design for Manufacturing and the Life Cycle Conf 2011
DOI: 10.1115/detc2011-47923
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Design Trends Using Perceptive Tests Based on an Interactive Genetic Algorithm

Abstract: To avoid flops, the control of the risks in product innovation and the reduction of the innovation cycles require valid and fast customer’s assessments. An Interactive Genetic algorithm is proposed for eliciting user’s perceptions concerning the shape of a product, in order to stimulate creativity and detecting design trends. Interactive users’ assessment tests are conducted on virtual products, for capturing and analyzing users’ responses. The IGA is interfaced with a CAD software (CATIA V5) and allows the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This method has been used for example to capture aesthetic intention of participants for the design of cartoons (Gu et al, 2006), car silhouettes (Yannou et al, 2008) or for preference modeling (Kelly et al, 2011). IGA have also been tested in our previous studies for the design of drinking glasses (Poirson et al, 2011) or car dashboards (Poirson et al, 2013) which have confirmed their utility in extracting designs trends and to obtain a final product solution that optimizes a determined semantic dimension. IGA have the great advantage of not needing restrictive assumptions concerning the preference model of the participant.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used for example to capture aesthetic intention of participants for the design of cartoons (Gu et al, 2006), car silhouettes (Yannou et al, 2008) or for preference modeling (Kelly et al, 2011). IGA have also been tested in our previous studies for the design of drinking glasses (Poirson et al, 2011) or car dashboards (Poirson et al, 2013) which have confirmed their utility in extracting designs trends and to obtain a final product solution that optimizes a determined semantic dimension. IGA have the great advantage of not needing restrictive assumptions concerning the preference model of the participant.…”
Section: Introductionmentioning
confidence: 99%